2023
DOI: 10.1037/xge0001257
|View full text |Cite
|
Sign up to set email alerts
|

Are the contributions of processing experience and prior beliefs to confidence ratings domain-general or domain-specific?

Abstract: Previous studies on domain generality of metacognition showed inconsistent results about cross-domain correlation of metacognitive resolution, which might result from the varied relationship between actual performance and the information utilized during confidence rating across tasks. The current study investigated metacognitive domain generality using the Bayesian inference model for metamemory (BIM), which suggests that individuals integrate current processing experience and their prior beliefs to construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 62 publications
(147 reference statements)
3
7
0
Order By: Relevance
“…100. These results indicated that the dot discrimination task was easier than the color discrimination task, consistent with the findings observed in previous study (Hu et al, 2023).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…100. These results indicated that the dot discrimination task was easier than the color discrimination task, consistent with the findings observed in previous study (Hu et al, 2023).…”
Section: Resultssupporting
confidence: 93%
“…The procedure for the recognition memory test was similar to that in previous studies (e.g., Fleming et al, 2014; Hu et al, 2023; McCurdy et al, 2013). The task contained four blocks, and in each block participants were first presented with 50 words simultaneously on the screen (arranged in 10 rows and five columns) and asked to memorize as many words as possible (see Figure 9A).…”
Section: Methodsmentioning
confidence: 99%
“…The estimated value of d' was reliably greater in the dot discrimination task (M = 2.23, SD = 0.35) than color discrimination task (M = 1.12, SD = 0.33), t( 49 These results indicated that the dot discrimination task was easier than the color discrimination task, consistent with the findings observed in previous study (Hu et al, 2022).…”
Section: Resultssupporting
confidence: 87%
“…In Experiment 1, participants were asked to perform two 2AFC perceptual decision tasks, including a color discrimination task and a dot discrimination task, and give their response using a 6-point confidence rating scale. The two tasks were taken from a previous study by Hu et al (2022), in which the performance was reliably higher for dot discrimination task than color discrimination task (i.e., the dot discrimination task is easier). Here we used 2AFC tasks because participants' response in a 2AFC task can be characterized by SDT with two distributions that have equal variance, leading to simplicity in mathematics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation